Polysoaps/Stabilizers/Nitrogen-15 NMR
DOI: 10.1007/bfb0025228
|View full text |Cite
|
Sign up to set email alerts
|

Molecular concepts, self-organisation and properties of polysoaps

Abstract: The article reviews water-soluble polymers characterized by surfactant side chains, and related amphiphilic polymers. Various synthetic approaches are presented, and rules for useful molecular architectures are given. Models for the self-organization of such polymers in water are presented comparing them with the micellization of low molecular weight surfactants. Highlighting key properties of aqueous polysoap solutions such as viscosity, surface tension and solubilization power, some structure-property relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0
4

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(132 citation statements)
references
References 436 publications
2
126
0
4
Order By: Relevance
“…Due to the use of heavy metals as catalysts during the synthesis of PET bottles, there are concerns regarding human expose (in particular by the leaching of antimony into drinking water) [52]. Nonetheless, if plastic bottle manufacturers consider the contamination during the manufacturing process and wash the bottles before their first use, the degree of exposure to these contaminants will be reduced [53].…”
Section: Porous Carbons From Petmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the use of heavy metals as catalysts during the synthesis of PET bottles, there are concerns regarding human expose (in particular by the leaching of antimony into drinking water) [52]. Nonetheless, if plastic bottle manufacturers consider the contamination during the manufacturing process and wash the bottles before their first use, the degree of exposure to these contaminants will be reduced [53].…”
Section: Porous Carbons From Petmentioning
confidence: 99%
“…Their strategy consisted of a repetitive sequence of in situ carboxyl group activation and condensation reactions. Kakimoto and coworkers synthesized hb polyamides [52] using p-phenylenediamine or 4,4 0 -oxyphenylenediamine as A 2 monomer and trimesic acid as B 3 building block. The structures of these A 2 and B 3 monomers are shown in Scheme 1.…”
Section: Synthesis Of Aromatic Hyperbranched Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Above them, the advantage of RAFT polymerization is applicable to a wide range of monomers under a broad range of experimental conditions. We previously synthesized poly(sodium2-(acrylamido)-2-methylpropanesulfonate)-blockpoly(sodium6-(acrylamido)hexanoate) (PAMPS-PAaH) via RAFT radical polymerization, and investigated its pH-induced association behavior in 0.1 M NaCl aqueous solutions with dynamic light scattering (DLS), static light scattering (SLS), 1 H NMR relaxation, and fluorescence probe techniques [11]. The experimental data indicated that PAMPS-PAaH forms polymer micelles conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They have been mainly used either in templated polymerization or in emulsion polymerizations. [2][3][4][5][6][7][8][9] When surfmers are copolymerized with conventional monomers, the obtained polymers are generally used for their amphiphilic properties in different media. Very little has been published on the bulk properties of surfmer-containing copolymers.…”
Section: Introductionmentioning
confidence: 99%